2008
DOI: 10.1158/1535-7163.mct-08-0074
|View full text |Cite
|
Sign up to set email alerts
|

A novel mode of action of YC-1 in HIF inhibition: stimulation of FIH-dependent p300 dissociation from HIF-1α

Abstract: Hypoxia-inducible factor (HIF)-1 plays a key role in tumor promotion by inducing f60 genes required for tumor adaptation to hypoxia; thus, it is viewed as a target for cancer therapy. For this reason, YC-1, which downregulates HIF-1A and HIF-2A at the post-translational level, is being developed as a novel anticancer drug. We here found that YC-1 acts in a novel manner to inhibit HIF-1. In the Gal4 reporter system, which is not degraded by YC-1, YC-1 was found to significantly inactivate the COOH-terminal tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(84 citation statements)
references
References 42 publications
1
82
0
1
Order By: Relevance
“…23 Dong et al reported that hippocampal apoptosis was aggravated by YC-1, which was an inhibitor of HIF-1a and HIF-2a. 24,25 We found YC-1 effectively suppressed the protein level of HIF-1a and HIF-2a in AGE1.HN and PC12 cells exposed to hypoxia. When AGE1.HN and PC12 cells transfected with YC-1 or siHIF-1a or siHIF-2a and exposed to hypoxia, we found that YC-1 and siHIF-1a reversed the effect of hypoxia on .HN and PC12 cells were transfected with BCL-2 plasmid or controls and then exposed to hypoxia.…”
Section: Discussionmentioning
confidence: 74%
“…23 Dong et al reported that hippocampal apoptosis was aggravated by YC-1, which was an inhibitor of HIF-1a and HIF-2a. 24,25 We found YC-1 effectively suppressed the protein level of HIF-1a and HIF-2a in AGE1.HN and PC12 cells exposed to hypoxia. When AGE1.HN and PC12 cells transfected with YC-1 or siHIF-1a or siHIF-2a and exposed to hypoxia, we found that YC-1 and siHIF-1a reversed the effect of hypoxia on .HN and PC12 cells were transfected with BCL-2 plasmid or controls and then exposed to hypoxia.…”
Section: Discussionmentioning
confidence: 74%
“…YC-1 induces HIF-1a protein degradation (64), and it inhibits the translation of HIF-1a mRNA via suppression of the PI3K/AKT/mTOR pathway and Akt/NF-kB signaling (11). Furthermore, YC-1 regulates HIF-1a functional activity at the posttranslational level (65).…”
Section: Hif-1 Inhibition Tumor Microenvironment and Response To Ramentioning
confidence: 99%
“…Hypoxia, a reduction in tissue oxygen tension due to inadequate oxygen supply, is a common phenomenon that occurs in a majority of solid tumours in humans (4). The presence of hypoxia is associated with aggressive tumour progression, resistance to chemotherapy and radiation, and poor prognosis (5,6).…”
Section: Introductionmentioning
confidence: 99%